The error analysis of learning mandarin endocentric phrases among the Malay students in Malaysia / Mok Soon Sim, Lau Suk Khin and S. Suchithra K. Sankaran - Mok, Soon Sim; Lau, Suk Khin; K. Sankaran, S. Suchithra (Akademi Pengajian Bahasa, 2019)
The Mandarin language has gained currency in the Malaysian education landscape. Particularly in tertiary educational settings in Malaysia, it is common to find Malay students learning the Mandarin language. Universiti Teknologi MARA (UiTM) is the largest university in Malaysia and it has the greatest number of Malay students learning Mandarin as a third language in the country. Almost all of the Malay students who study the Mandarin language at the university have no background in Mandarin. They are inevitably influenced by their mother tongue which is the Malay language. This paper aims to analyze Endocentric Mandarin phrasal errors commonly made by Malay students while studying Mandarin in UiTM. In addition, some teaching methods are also recommended to guide those involved in teaching and learning Mandarin. This study is conducted using a mixed method approach. Two research instruments were used in this study, that is question papers and interviews. 40 Malay students who were taking Introductory Mandarin Level II course in UiTM Shah Alam campus were chosen as the survey respondents. The results of the research revealed that there are 4 types of errors commonly made by Malay students in learning the Mandarin Endocentric Phrases, namely: (i) Omission of Measure Words, (ii) Reversed string order of Endocentric Phrases, (iii) Errors in Using Demonstrative Pronouns and (iv) Excess of the particle “de”. The most obvious mistake is the Omission of Measure Words and the Reversed string order of Endocentric Phrases due to the first language disruption. These errors have often resulted in structural and morphological inaccuracies.